The role of the manager and foresight in crisis scenarios - Lora-Guzmán, Harold S.; Prieto-Flórez, Javier (EFIM Ediciones, 2021)
This article exposes the exercise of strategic planning and foresight as an essential tool in the exercise of modern management, given by the scenarios of uncertainty and complexity that can be seen in the different economic sectors. Some aspects that are considered when studying these uncertainties are the environmental, economic, social, political dimensions and those intrinsic associated with the characteristics of the human being. What is expressed in these documents is part of a research work that has been carried out by the authors in cooperation with the Chamber of Commerce of Cartagena de Indias and the government of Bolívar; In which it is intended to demonstrate the importance of studying future scenarios that contribute to making better decisions in the exercise of decision-making and management in SMEs; highlights the importance of this methodology and the use of contingent strategic alternatives to define institutional policies in times of crisis that contribute to the economic and social development of the region.